2022
DOI: 10.3389/fmars.2022.975875
|View full text |Cite
|
Sign up to set email alerts
|

Extraction efficiency of different microplastic polymers from deep-sea sediments and their quantitative relevance

Abstract: An increasing number of methods for extracting microplastic particles from marine sediments have been published but without evaluating the extraction efficiency. Furthermore, while most of the procedures developed have been applied to sandy sediments from shallow water habitats, specific and standardized procedures for deep-water sediments (> 200 meters deep) are limited. In this study, we describe a specific protocol for extracting microplastics (2- 1000 µm) from deep-sea sediments and for quantifying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 84 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…The low abundance of MPs recorded at the majority of sites would indicate that none of these are accumulation areas and may reflect recent deposition, may be indicative of underwater activity in the area, and their distance to terrestrial sources. Canensi et al 46 and Villanova-Solano et al 51 similarly found no relationship between water depth and the density of MPs.…”
Section: ■ Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The low abundance of MPs recorded at the majority of sites would indicate that none of these are accumulation areas and may reflect recent deposition, may be indicative of underwater activity in the area, and their distance to terrestrial sources. Canensi et al 46 and Villanova-Solano et al 51 similarly found no relationship between water depth and the density of MPs.…”
Section: ■ Discussionmentioning
confidence: 96%
“…45 Caution needs to be taken when making inferences where MP results have low abundances and/or no replicates. Furthermore, Canensi et al 46 found that partitioning sediments of 250−50 g aliquots favors the extraction in the size range of 2−1000 μm with extraction efficiency changing depending on polymer type.…”
Section: ■ Discussionmentioning
confidence: 99%